The Intersection of Psycholinguistics and Systemic Functional Linguistics in Textbooks - Ієронім Канггунг Даронг; Ерна Мена Німан (Психолінгвістика)
Purpose. Textbooks have an important role in learning foreign languages, especially in shaping students' linguistic competencies. This study analyzes elementary school English textbooks with psycholinguistics theory and Functional Systemic Linguistics (SFL) approaches to assess their suitability with students' cognitive development and language acquisition.